The Chinese Corporate Tax System: A Factor in Attracting and Maintaining Foreign Investments (London Journal of Research In Management & Business, 2025)
Aiming to reduce tax costs and social security contributions in the manufacture of products destined for other countries, China reorganized its legislation and improved its entire executive/administrative foreign trade policy by accelerating the renovation and construction plan for approximately one thousand new ports/terminals along its extensive coastline. China has also changed its tax system by granting specific benefits to foreign enterprises (FEs) and foreign-invested enterprises (FIEs) present in one of the five special economic zones (SEZs) or that establish themselves in areas of technological economic development (ETDZs). Even after its acceptance as the 143rd member country of the WTO, with many concessions, the Chinese corporate tax system continues to be a factor in attracting and retaining foreign investment
Keywords: Chinese corporate tax system; Foreign investment; Export of Chinese products